A REVITALIZATION OF IJMAK TOWARDS FORMATION CONTEXTUAL OF ISLAMIC LEGAL THEORY - Zayad Abd. Rahman; Ilham Tohari (Jurnal Pembaharuan Hukum, 2022)
Ijmak, which today is defined as the consensus of the mujtahid of the whole world and occupies the third position in the hierarchy of sources of Islamic law, is not widely used by scholars. Ijmak with this kind of definition is certainly impractical and tends to be idealistic. Because it is impossible to reach a unanimous agreement regarding the furu'iyyah matter, it has become a matter of fact that differences of views are necessary. This research seeks to unearth ijmak artifacts in their historical development to find a true definition of ijmak. This study concluded that ijmak in the early era of its appearance was not the same ijmak as today. The old ijmak—in the era of Caliph Abu Bakr—with today's ijmak seems to have diametrical differences. Ijmak used to be democratic in tone (all people can have faith), open to criticism, and flexible in change. Whereas today the ijmak becomes the authority of the mujtahid, closed to criticism, and rigid. Even opposing the valid ijmak is considered a form of fussiness. In the context of Indonesianness, ijmak is synonymous with local wisdom that develops in the community. One example: polygamy is a taboo in Indonesian society, although Islamic law and state law it does not prohibit it.